Obtenção e caracterização do sistema compósito alginato de sódio-dióxido de titânio em formas de pó e de membrana - Lisboa, Marcia Severiano (2011)
The alginates are copolymers of 1→4-linked β-D-mannuronic acid (M) and α-Lguluronic acid (G) residues that are arranjed in a block structure along a linear chain. Titanium dioxide, TiO2, is a ceramic material and can exist in three distinct crystallography forms: anatase, brookite and rutile. composites of organic and inorganic materials have better properties than the components alone. Thus, this study aims to synthesize, characterize and analyze the composite NaAlg-TiO2 in the form of powder and film. The synthesis of composite powders was performed using the sol-gel process and obtain the composite film was performed using the slow evaporation process, then the composites were analyzed by infrared spectroscopy, fluorescence x ray, thermal analysis, attenuated total reflection (ATR), x ray diffraction and impedance spectroscopy. The X ray diffraction patterns of composite powders show that with increasing calcination temperature, there were no complete transition of rutile-anatase crystalline phase, since at all temperatures studied (300, 500, 700, 900 and 1100ºC) were observed peaks of anatase phase. Thermal analysis shows that at 400°C caused the decomposition of sodium alginate in sodium carbonate and above 600°C, we observe an exothermic peak related to the decomposition of sodium carbonate and in the presence of titanium dioxide becomes sodium titanate. The XRD results confirm the formation of sodium carbonate at 700ºC and the formation sodium titanate in the temperature range 900-1100ºC. The sodium titanate influenced the electrical properties of the material, because with increasing temperature there was a decrease in conductivity, probably due to the creation of Ti vacancies, since the sodium can induce the reduction of surface Ti4+ ions into Ti3+ species. The infrared spectra of the composites in the form of powder and film showed a small shift in the bands compared to the spectrum of pure alginate, indicating that these shifts, even small ones, have evidence of miscibility between the polymer and ceramic material